Identification and antifungal susceptibility of Candida species isolated from the urine of patients in a university hospital in Brazil - Espindola Lima, Glaucia Moreira; Nunes, Maina de Oliveira; Chang, Marilene Rodrigues; Sousa Tsujisaki, Rosianne Assis de; Nunes, Joslaine de Oliveira; Taira, Cleison Ledesma; Thomaz, Danilo Yamamoto; Barbaro Del Negro, Gilda Maria; Mendes, Rinaldo Poncio [UNESP]; Miranda Paniago, Anamaria Mello (Inst Medicina Tropical Sao Paulo, 2017)
The aim of this study was to identify Candida spp. isolated from candiduria episodes at a tertiary hospital in the Midwest region of Brazil, and to determine their susceptibility profiles to antifungal compounds. From May 2011 to April 2012, Candida spp. isolated from 106 adult patients with candiduria admitted to the University Hospital of the Federal University of Mato Grosso do Sul were evaluated. Both, species identification and susceptibility testing with fluconazole-FLC, voriconazole-VRC, and amphotericin B-AmB were carried out using the Vitek 2. To discriminate species of the C. parapsilosis complex, a RAPD-PCR technique using the RPO2 primer was performed. From the total of 106 isolates, 42 (39.6%) C. albicans and 64 (60.4%) Candida non-albicans (CNA) -33 C. tropicalis, 18 C. glabrata, 5 C. krusei, 4 C. parapsilosis sensu stricto, 2 C. kefyr, 1 C. lusitaniae, and 1 C. guilliermondii were identified. All isolates were susceptible to AmB and VRC, whereas all C. glabrata isolates presented either resistance (5.6%) or dose-dependent susceptibility (94.4%) to FLC. The study of Candida spp. and their resistance profiles may help in tailoring more efficient therapeutic strategies for candiduria.
Keywords: Urine infections; Antifungal agents; Nosocomial candiduria; Candida species; Antifungal susceptibility